Peranan Cost Controller Dalam Pengendalian Biaya Operasional Pada Swiss-Belhotel Silae Palu - Tito Yanuar Dana; Moh. Ali Murad; Wiri Wirastuti (Journal of Management and Social Sciences, 2023)
One of the supporters of the Ministry of Tourism and Creative Economy in improving the economy, especially in the field of tourism destinations, namely the Hospitality Industry. The main purpose of the hotel industry is as a means of accommodation for temporary accommodation for guests who come from various places and places to conduct business meetings, seminars, wedding receptions, workshops, national meetings and other activities. In addition, the role of the hospitality industry is very helpful for tourists who are visiting to travel with lodging services provided by hotels. To compete in the hotel industry requires a strong management structure, especially in terms of controlling operational costs. Therefore, the company needs a cost control. Cost Control is one component to support the running of business activities in hotel companies. The role played by the cost controller is inventory, supervision and control of hotel spending costs to achieve.